Diversity of Treegourd (Crescentia cujete) Suggests Introduction and Prehistoric Dispersal Routes into Amazonia - Moreira, Priscila A.; Aguirre-Dugua, Xitlali; Mariac, Cédric; Zekraoui, Leila; Couderc, Marie; Rodrigues, Doriane P.; Casas, Alejandro; Clement, Charles R.; Vigouroux, Yves (Frontiers in Ecology and Evolution, 2017)
The use and dispersal of domesticated plants may reflect patterns of early human diffusion of technologies and lifestyles. Treegourd (Crescentia cujete) has fruits with ancient utilitarian and symbolic value in the Neotropics. We assessed diversity based on chloroplast (SNPs), nuclear (SSR) markers, and fruit shapes of cultivated treegourds and wild relatives across Amazonia and Mesoamerica in order to discuss hypothesis of dispersal routes and diversification of fruits along its distribution. The haplotype network showed three distinct groups: Crescentia amazonica, wild Mesoamerican C. cujete, and cultivated C. cujete from Brazilian Amazonia and Mexico. Mexico and Brazil shared two haplotypes, with slightly different distributions in Amazonia. The most divergent haplotype is well-represented in Eastern Amazonia. Nuclear differentiation between Mesoamerican wild and cultivated C. cujete is relatively low (FST = 0.35), compared with Amazonian cultivated (FST = 0.45–0.61). Differentiation is also higher between wild C. amazonica and cultivated C. cujete (FST = 0.57), but modest within cultivated C. cujete from Amazonia and Mexico (FST = 0.04), with higher genetic similarity in northwestern Amazonia. Mexico and Amazonia showed similar chloroplast nucleotide diversity (4.66 × 10−2 and 5.31 × 10−2, respectively), although sample sizes are very different. Except in Northwestern and Eastern Amazonia, we found ample genetic homogeneity of cultivated C. cujete across Amazonia, but highest morphological diversity in the Northwest, with fruit shapes that are absent in Mexico. We conclude that treegourds introduced into the Amazon Basin and Mexico share a common ancestry with a currently unknown origin. The patterns of genetic diversity across Amazonia allow two hypotheses of the routes of introduction: a northwestern introduction into the Negro and Solimões Rivers, and an eastern introduction from the coastal Guianas into the Amazonas River. The dispersal into Amazonia followed previously proposed routes of human and plant migrations. The contrasting fruit shape diversity suggests different utilitarian demands and cultural preferences for treegourd fruits between Mexico and Amazonia.